Evaluating the role of composition and local structure on alkali out‐diffusion in glasses for thin‐film solar cells. Issue 2 (5th October 2020) - Bansal, Neetu; Gupta, Mukul; Mohanty, Bhaskar Chandra; Singh, Kulvir
Abstract: The presence of alkali ions has reportedly improved the performance of CIGS/CZTS–based thin‐film solar cells. The out‐diffusion of the alkali ion, in particular, Na, from the glass substrate offers a facile scalable route of supplying the alkali ions during the growth of the absorber layer. In this work, we demonstrate the diffusion of different alkali ions (Li/Na/K) from composition tuned glasses with intentionally incorporated excess alkali ions into a thin Mo film, typically used as a bottom electrode in solar cells. We also evaluate the physical, mechanical, and thermal properties of the glasses for suitability as a substrate in thin‐film deposition. The out‐diffusion of alkali ions to the overlayer is found to be critically influenced by the composition and the local structure of the glasses. The Na ions exhibit the highest extent of diffusion among the alkali ions present in glass substrates, while that for the K‐ions is the lowest. For the glasses with mixed alkali ions, the presence of Li facilitated the out‐diffusion of Na, whereas K ions appear to inhibit the same. Differently with the existing reports, we show that the activation energy and the presence of Ca ions as additional modifiers play a crucial role in the transport mechanism of the ions. In addition, the synthesized glasses exhibit hardness of the order 5‐7 GPa, density ~2.55 g cm ‐3 . The glass transition temperature lies between 535 and 580°C and the coefficient of thermal expansion 8.5‐10 ppm/K, which is highly suitable for use as substrates in thin‐film solar cells. Abstract : Composition‐tuned glasses have been designed and investigated the role of its composition and local structure on out‐diffusion of alkali ions into a thin Mo overlayer for potential integration in thin film photovoltaic technology.